ENGLISH LANGUAGE TEACHING FOR STUDENTS WITH SPECIAL NEEDS:PEDAGOGICAL PRACTICES AND SUPPORT SYSTEMS - Nurlaila Husain; Sri Widyarti Ali; Rasuna Rasid Talib; Moon Hidayati Otoluwa; Sartin T. Miolo (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study explores the pedagogical practices and support systems surrounding English language teaching for students with special needs in Sekolah Luar Biasa (SLB), with a focus on two experienced teachers in Gorontalo City. Using a qualitative descriptive design, data were collected through semi-structured interviews, capturing insights from teachers instructing students with diverse disabilities, including visual, hearing, intellectual, physical, and developmental impairments. The findings indicate that teachers adapt lesson plans, design their own modules, and employ multimodal resources such as flashcards, posters, videos, and educational applications. Instruction is personalized based on initial assessments to align with each student's abilities. However, challenges persist, notably the lack of specialized training in English teaching for students with disabilities, inconsistent parental involvement, and limited collaboration with external educational stakeholders. While institutional support—such as policy provisions and instructional materials—is evident, external partnerships remain underdeveloped. The study underscores the need for systemic interventions, including targeted professional development, strengthened home-school collaboration, and inter-agency cooperation to ensure inclusive and effective English language education for learners with special needs.